Bangsa Implementasi Pancasila Untuk Mencegah Isu Radikalisme Dalam Bingkai Kebhinekaan: Pancasila dan isu Radikalisme dalam bingkai kebhinekaan - Robin Muhammad; Slamet Widodo (LPPM Press, 2022)
The Indonesian nation is a pluralistic nation that has various cultural, linguistic, ethnic, racial, customary and religious diversity. The cultural diversity of the Indonesian nation can trigger conflict and has the potential to give rise to various radical understandings and movements, both in the name of religion, ethnicity, and class. However, in reality the radicalism movement emerged not only due to racial differences, but also global, political, and social disparities in society. The method of writing this article is by using the literature review method. The purpose of this paper is to analyze how the implementation of Pancasila values ​​in an effort to prevent the spread of radicalism and radicalism in Indonesia. At this time the implementation of Pancasila values ​​in people's lives is fading, this is caused by a lack of awareness and understanding of the community about the meaning and significance of Pancasila values. Joint actions or efforts are needed in implementing Pancasila values ​​in the life of society, nation and state in preventing the spread of radicalism and understanding movements in order to maintain the integrity of the Indonesian nation with unity and integrity.